2017
DOI: 10.1007/s12149-017-1189-9
|View full text |Cite
|
Sign up to set email alerts
|

FMISO accumulation in tumor is dependent on glutathione conjugation capacity in addition to hypoxic state

Abstract: Objective 18F-fluoromisonidazole (FMISO), a well-known PET imaging probe for diagnosis of hypoxia, is believed to accumulate in hypoxic cells via covalent binding with macromolecules after reduction of the nitro group. Previously, we showed the majority of 18F-FMISO was incorporated into low-molecular-weight metabolites in hypoxic tumors, and the glutathione conjugate of reduced FMISO (amino-FMISO-GS) distributed in the tumor hypoxic regions as revealed by imaging mass spectrometry (IMS). The present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…A group in Japan studied the mechanism of NI based 18 F-FMISO binding in nude mice by implanting cells from the human FaDu cancer line [14,33,34]. They found that the majority of the tumor radioactivity was from low molecular weight metabolite, glutathione (GST) conjugate of amino-FMISO (amino-FMISO-GH) [14,34,35]. Amino-FMISO-GH is highly hydrophilic and cannot diffuse out of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A group in Japan studied the mechanism of NI based 18 F-FMISO binding in nude mice by implanting cells from the human FaDu cancer line [14,33,34]. They found that the majority of the tumor radioactivity was from low molecular weight metabolite, glutathione (GST) conjugate of amino-FMISO (amino-FMISO-GH) [14,34,35]. Amino-FMISO-GH is highly hydrophilic and cannot diffuse out of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Amino-FMISO-GH is highly hydrophilic and cannot diffuse out of the cell. However, it could efflux out via the adenosine triphosphate (ATP) dependent multi-drug resistant protein (MRP-1) [34,36], which is highly expressed in pancreatic tumor cells [5,[37][38][39] and is responsible for drug resistance. A similar efflux of amino-FAZA-GH could explain the non-trapping of 18 F-FAZA in hypoxic tissue and hence the estimation of non-zero with kinetics modelling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 F-labelled 2-nitroimidazole-based markers have been widely used for PET imaging of hypoxia. In an anoxic environment reduction of the NO 2 moiety of 2-nitroimidazole by nitroreductases produces highly reactive intermediates which bind to many macromolecules and also undergo glutathione conjugation [81]. 18 F-fluoromisonidazole ( 18 F-FMISO) was the first PET tracer for hypoxic imaging to be developed and has subsequently been the most extensively used, with accumulation having been demonstrated in human glioma, head and neck squamous cell carcinomas (HNSCC), breast, lung and renal tumours.…”
Section: Hypoxia Imagingmentioning
confidence: 99%